A scale development study on the expectations of university students from the accounting course in the digitalization process - Ayşe Kurtlu; Mehmet Uçar (Anali Ekonomskog fakulteta u Subotici, 2022)
Digitization has become an inevitable part of life, affecting all systems. Today, where technological developments are increasing rapidly, and almost everything can be done with mobile devices, all sectors and individuals have started to take a more place in digital. Since the 20th century, the accounting profession has undergone significant changes, especially with the spread of the internet and technological developments, and many accounting practices have been transferred to digital environments. The traditional methods of accounting education cause the candidate students to grow away from the digitalized sector. For this reason, the digital transformation process in the accounting profession should also be started in accounting education. To train professionals who will meet the needs in the digital age, accounting education should be supported by changing technology, and students should be equipped in this regard by using digital education technologies such as augmented reality (AR) and simulation in courses. In the study, a scale was developed to determine the expectations of the students from the accounting course during the digitalization process. As a result of the study, it was determined that the scale was divided into two sub-dimensions: expectation from digital education technologies and expectation from traditional expression in the accounting course.